The Use of Volunteering as an Indirect Source of Financing for Public Benefit Activity on the Example of Polish Foundations and Associations - Anna STASZEL; Pawel ZIENIUK (Communications of International Proceedings, 2020)
Public benefit organisations are increasingly using volunteers, i.e. people who provide services voluntarily and without remuneration. Simultaneously, an increase in interest can be observed in problems such as the need for legal regulation of volunteering, elimination of tax barriers or ensuring the reimbursement of necessary costs incurred by volunteers in connection with the provision of services for the organisation. In Poland, there are detailed legal regulations on volunteering, compliant with EU requirements, which were presented in this study.  It also presents the results of the authors' own research, carried out on a sample of 100 randomly selected public benefit organisations operating in the form of foundations and associations, conducting their activities in Poland. The aim of the research was to present the interrelationships between the number of volunteers involved in the organisation's activities and factors specific to the organisation, such as: territorial range, number of beneficiaries, duration of public benefit activities, number of employees employed and the amount of operating costs incurred and income generated. The research was performed on the basis of data from financial and substantive statements of the selected organisations. The following statistical methods were used to verify the formulated hypotheses: t test for independent samples and ANOVA variance analysis. The results of the research allow for a statistically significant correlation between the number of volunteers and the territorial range of activities carried out by the organisations and the amount of income generated. Thus, it can be said that voluntary activity is more prevalent in organisations with lower incomes which, without the help of volunteers, would not be able to carry out the current range of public benefit activities, due to a lack of resources to recruit staff and finance salaries.
Keywords: volunteering; public benefit organizations; foundations; associations; sources of financing for public benefit activities